2013
DOI: 10.5005/jp-journals-10006-1212
|View full text |Cite
|
Sign up to set email alerts
|

Eclampsia: Maternal and Fetal Outcome

Abstract: Eclampsia is the leading cause of maternal and perinatal mortality as well as morbidity. This prospective study was carried out at a tertiary institute from Jan 2008 to Dec 2010. Aim and objectives (1) To evaluate the rate of eclampsia in antenatal women attending our hospital, (2) to evaluate the epidemiological factors and clinical presentation in women with eclampsia, (3) to analyze the maternal and perinatal outcome in women with eclampsia, and (4) to formulate strategies to improve the maternal and perin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Antepartum eclampsia was the commonest in our study around 69.8%, Which is comparable to study by Anuja Bhalerao et al who reported antepartum eclampsia of 70.91%. 9 But postpartum eclampsia was common in study by Chames MC et al because of earlier detection of preeclampsia and prophylactic magnesium sulphate. 10 40.3% of patients were in gestational age of 32-36 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Antepartum eclampsia was the commonest in our study around 69.8%, Which is comparable to study by Anuja Bhalerao et al who reported antepartum eclampsia of 70.91%. 9 But postpartum eclampsia was common in study by Chames MC et al because of earlier detection of preeclampsia and prophylactic magnesium sulphate. 10 40.3% of patients were in gestational age of 32-36 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…6 We observed 48% preterm births and similar results were reported by Bhalerao et al as preterm deliveries 42% and term 58% deliveries. 18 In a study by Khanum et al there were 66% live births, 21% still births and 17% cases of neonatal deaths. 11 George IO et al reported neonatal deaths due to birth asphyxia in 33.3% cases; 22.2% by respiratory distress syndrome; 22.2% with prematurity; 16.7% with sepsis and 5.6% with jaundice.…”
Section: 5mentioning
confidence: 96%
“…18.18% cases were IUD and 27.27% cases were IUGR. 18 Sunita TH reported a 92% live birth rate and 8% still births. 6 We observed 48% preterm births and similar results were reported by Bhalerao et al as preterm deliveries 42% and term 58% deliveries.…”
Section: 5mentioning
confidence: 98%
See 1 more Smart Citation
“…Bhalero A. reported adverse maternal and prenatal outcome associated increased interval between onset of convulsion and delivery interval. 13 42.85% mothers died before delivery. Once a complication had already developed, magnesium sulphate could not prevent the sequel of complications.…”
Section: Discussionmentioning
confidence: 98%